2017
DOI: 10.3892/or.2017.5548
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-187 modulates epithelial-mesenchymal transition by targeting PTRF in non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) that negatively regulate gene expression play a key role in the development and progression of cancer. Aberrant expression of hsa-miR-187 (miR-187) has been reported in various malignancies. However, the function of miR-187 in tumor progression remains controversial and its role in non-small cell lung cancer (NSCLC) is poorly understood. In the present study, the role of miR-187 in the progression of NSCLC was investigated. Our results revealed that miR-187 was frequently upregulated in NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Six negative-relevant miRNAs were miR-187, miR-9-3, miR-490, miR-1258, miR-551a and miR-665; among these miRNAs, miR-187 has been found to be overexpressed in ovarian cancers 20 , can induce epithelial-mesenchymal transition (EMT) by targeting PTRF in non-small cell lung cancer 21 and promotes the growth and metastasis of gastric cancer by inhibiting FOXA2 22 . this result indicated that miR-187 possessed the potential to be a candidate for LIHC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Six negative-relevant miRNAs were miR-187, miR-9-3, miR-490, miR-1258, miR-551a and miR-665; among these miRNAs, miR-187 has been found to be overexpressed in ovarian cancers 20 , can induce epithelial-mesenchymal transition (EMT) by targeting PTRF in non-small cell lung cancer 21 and promotes the growth and metastasis of gastric cancer by inhibiting FOXA2 22 . this result indicated that miR-187 possessed the potential to be a candidate for LIHC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, PTRF inhibits the EMT process and suppresses the cell proliferation and metastasis (20). The downregulation of PTRF is associated with dysregulation of miRNAs and DNA methylation in cancer cells (20,30). Via bioinformatics analysis, the present study identified that PTRF is a potential target of miR-1301-3p.…”
Section: Discussionmentioning
confidence: 69%
“…For example, PTRF overexpression restores caveolae formation, reduces matrix metalloproteinase-9 expression and inhibits the migration of metastatic prostate cancer cells (29). In lung cancer, PTRF inhibits the EMT process and suppresses the cell proliferation and metastasis (20). The downregulation of PTRF is associated with dysregulation of miRNAs and DNA methylation in cancer cells (20,30).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that miR-187 plays an important role in cancer development [18]. Cai et al [33] found that miR-187 promotes cell migration and epithelial-mesenchymal transition (EMT) by targeting polymerase I and transcript release factor (PTRF) in NSCLC, and miR-187 potentially plays an oncogenic role in the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 97%